Niche Specialization and Functional Overlap of Bamboo Leaf and Root Microbiota - Zheng, Ying; Lin, Xinchun (Frontiers in Microbiology, 2020)
Leaves and roots harbor taxonomically diverse bacterial assemblages which enhance plant growth and performance by increasing nutrient supply and resistance to stress. An extensive investigation of bacterial diversity and composition between leaf and root microbiota of 15 bamboo species differing in rhizome types, lifeforms and sampling sites were conducted by high-through sequencing. The alpha diversity between leaf and root microbiota was not significantly different, whereas, their beta diversity differed remarkably. Niche specialization mainly in species from Actinobacteria was detected which prefer to colonize in roots than leaves. Community structure of leaf microbiota was highly resembled, however, the phylogeny inferred by host’s chloroplast data was incongruent with microbiota dendrogram, indicating that phylosymbiosis didn’t occur in bamboos and their associated microbiota. Large overlap in functional profiling of leaf and root-associated microbiota was found. Accordingly, we proposed that environmental conditions, structural variation and physiological differences between leaves and roots worked collaboratively for divergence of bamboo microbiota. This study confers to a robust knowledge of bamboo-microbe interaction and provides a list of bacterial lineages for investigation into specific plant-microbe interaction information of which could be used to enhance agricultural and forest productivity.